2019
DOI: 10.1016/j.jip.2019.107257
|View full text |Cite
|
Sign up to set email alerts
|

Infective juveniles of entomopathogenic nematodes (Steinernema and Heterorhabditis) secrete ascarosides and respond to interspecific dispersal signals

Abstract: Ascarosides are a modular series of signalling molecules that are widely conserved in nematodes where they function as pheromones with both behavioural and developmental effects. Here we show that the developmentally arrested infective juvenile (IJ) stage of entomopathogenic nematodes (EPN) secrete ascarosides into the surrounding medium. The exometabolome of Steinernema carpocapsae and Heterorhabditis megidis was examined at 0, 1, 7 and 21 days of storage. The concentration of several ascarosides (ascr#11, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
(80 reference statements)
2
11
1
Order By: Relevance
“…Consistent with the literature, Hartley et al 39 showed that as the ascaroside content increases during storage and overall nematode dispersal was reduced from 1 to 3 weeks. When the IJs are exposed to one week-storage medium associated with high dispersal, it stimulates the IJ dispersal as expected 39 . However, the 3-week storage medium with lower dispersal activity has a different ascaroside composition.…”
Section: Conclusion and Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Consistent with the literature, Hartley et al 39 showed that as the ascaroside content increases during storage and overall nematode dispersal was reduced from 1 to 3 weeks. When the IJs are exposed to one week-storage medium associated with high dispersal, it stimulates the IJ dispersal as expected 39 . However, the 3-week storage medium with lower dispersal activity has a different ascaroside composition.…”
Section: Conclusion and Discussionsupporting
confidence: 70%
“…In this study, S. carpocapsae IJs responded to pheromone extracts from consumed insect host cadavers of 8 different species of Steinernema and Heterorhabditis regardless of their foraging strategies. The literature and our current findings suggest that the pheromone mixtures have not diverged to the point where they are species specific 22,39,48 . However, the precise pheromone mix for each species remains to be discovered.…”
Section: Conclusion and Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Therefore, the accumulation of the ascaroside signal effectively functions to counteract the IJ recovery activity of the bacteria-derived IPS molecule, thus allowing the nematode to halt reproduction in a nematode population-dependent manner. Indeed, it appears that, similar to what has been reported in C. elegans, Heterorhabditis nematodes produce a range of ascaroside-like molecules that can regulate both nematode development and behaviour [124][125][126]. However, it remains to be seen if Photorhabdus makes any contribution to the production and/or modification of these, or any other, nematode-derived signals.…”
Section: The Nematode Contribution To Pathogenicity and Mutualismmentioning
confidence: 72%
“…Recent research has shown a commonality in the production of and sensitivity to ascaroside pheromones among free-living, plantparasitic, and insect-parasitic nematode species (Choe et al, 2012). Given that these small signaling molecules coordinate development, can have multi-trophic effects (Noguez et al, 2012;Hsueh et al, 2013;Zhao et al, 2016), and affect social behaviors (Hartley et al, 2019;Kaplan et al, 2020;Meng et al, 2020), it follows that they may be involved in trail following, particularly for species where individuals would face challenges to their reproductive success without signals to attract potential mates. However, the implication of ascarosides here is speculative and needs careful analysis of chemicals involved.…”
Section: Discussionmentioning
confidence: 99%